Identification of human TFIID components and direct interaction between a 250-kDa polypeptide and the TATA box-binding protein (TFIID tau). - Takada, R (1992)
Previous studies have indicated that human transcription initiation factor TFIID is a large complex that contains a TATA-binding polypeptide (TFIID tau or TBP) and other components that qualitatively alter promoter interactions and are uniquely required for activator-dependent (versus basal) transcription. TFIID tau-specific antibody columns have been employed to identify a number of human TFIID polypeptides that are tightly associated with TFIID tau. These differ in size from polypeptides in known general initiation factors, including the initiator-binding factor (TFII-I) which shares some promoter binding characteristics with TFIID. The largest component (p250) identified in TFIID was shown to interact directly and tightly with TFIID tau, suggesting that it may play a major role in the assembly of the TFIID complex.